A Design of Power Amplifier using Enhanced Simple Real Frequency Technique - Golestanifar, Alireza; Karimi, Gholamreza; Lalbakhsh, Ali (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
In this paper, a novel discrete wide-band microstrip power amplifier (PA) is designed and fabricated based on the enhanced simple real frequency technique (ESRFT) to achieve a higher power added efficiency (PAE) over a wide frequency range compared to the conventional simple real frequency technique (SRFT). To compare the ESRFT with the SRFT, a basic PA using the SRFT is designed additionally. The ESRFT applies the feedback effects that play an important role in the PA design process, especially for high-frequency applications. Unlike the SRFT, the ESRFT considers both the back-end and the front-end impedance of the active device, while it is loaded by the designed input matching network (IMN) and the output matching network (OMN), respectively. The parasitic feedback elements of the transistor disturb the designed IMN and OMN. Therefore, an iterative method can converge to a better result. The matching networks (MNs) are modeled as a single matching problem, formulated and calculated in the Richard domain. The MNs are constructed by cascading microstrip unit elements (UEs) to obtain a wide-band simple structure. The characteristic impedances of the UEs are derived using the Richard extraction process. The fabricated PA shows good agreement between the simulation and measurement results. It has a wide-band gain of up to 13 dB from 0.8 GHz to 1.6 GHz, with a maximum PAE of about 70% that has been improved compared to the designed basic PA. Furthermore, the third harmonic is suppressed up to 25 dBc.